Time duration of post-activation performance enhancement (PAPE) in elite male sprinters with different strength levels - Guo, Wenxia (2022)
(1) Purpose: This study aimed to explore the time duration of post-activation performance enhancement (PAPE) in elite male sprinters with different strength levels. (2) Methods: Thirteen elite male sprinters were divided into a strong group (relative strength: 1RM squat normalized by body mass of ≥ 2.5; n = 6) and a weak group (relative strength of < 2.5; n =7). All sprinters performed one static squat jump (SSJ) at baseline and 15 s, 3 min, 6 min, 9 min, and 12 min following an exercise protocol including three reps of a 90% 1RM back squat. Two force plates were used to determine the vertical jump height, the impulse output, and the power output for all SSJs. (3) Results: Significant improvements in vertical jump height and peak impulse were observed (p < 0.05) at 3, 6, and 9 min, without significant between-group differences. The peak power had a significant increase in 3 min (p < 0.01) and 6 min (p < 0.05), with also no significant difference between-group differences. Moreover, the stronger subjects induced a greater PAPE effect than the weaker counterparts at 3, 6, and 9 min after the intervention. The maximal benefit following the intervention occurred at 6 min and 3 min after the intervention in the stronger and weaker subjects, respectively. (4) Conclusions: The findings indicated that three reps of a 90% 1RM back squat augmented the subsequent explosive movement (SSJ) for 3–9 min in elite male sprinters, especially in stronger sprinters.